1-Butyl-3-Methylimidazolium Chloride Ionic Liquid as Inhibitor for Corrosion Protection of Mild Steel in Acidic Media - A. Ahmad Tarmizi, A; Peter, L; Ahtoi, D; Yusof, R; N.A. Syed Ismail, S; A. Tholibon, D (International Journal of Engineering and Technology, 2019)
Corrosion inhibitor is a substance added to the corrosive environment in small quantities to reduce the corrosion a metal. The addition of inhibitors will reduce the corrosion rate of the metal by retarding the corrosion process on the metal surface. Thus, this study focused on the study of the effectiveness of 1- butyl-3-methylimidazolium chloride ([EMIM]Cl) ionic liquid as an inhibitor for corrosion protection of mild steel. Two different concentrations of [EMIM]Cl (0.05 M and 0.5 M) were tested into different concentrations of sulphuric acid (0.05M, 0.10 M, 0.15 M, 0.20 M and 0.25 M). Weight loss measurement was used to determine the effectiveness of the [EMIM]Cl as inhibitor for corrosion protection. Results showed that acid concentrations play an important role for the corrosion protection process in the presence of the inhibitor. The weight loss increases as the concentration of the acid increased. The study also revealed that the concentrations of [EMIM]Cl ionic liquid effect the performance of the inhibitor. From this study, 0.5 M of [EMIM]Cl ionic liquid shows better corrosion performance compared to 0.05 M of [EMIM]Cl. At 0.25 M of sulphuric acid, the weight loss of untreated metal increased drastically from 0.0075 g at 0.5 hour to 0.0974 g at 24 hours. After treated with 0.5 M of [EMIM]Cl, the weight loss measurement slightly increased from 0.0027 g at 0.5 hour to 0.0179 g at 24 hours. This weight loss value is lower compared to mild steel treated with 0.05 M [EMIM]Cl which is 0.0469 g at 24 hours. The performance of the inhibitor in two different type of acid was also investigated. The morphology of the untreated mild steel and mild steel treated with [EMIM]Cl was investigated by scanning electronic microscopy (SEM)Â Â